2006
DOI: 10.1007/s00702-006-0435-4
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein promoter RsaI T-to-C polymorphism and the risk of Parkinson’s disease

Abstract: Increased alpha-synuclein expression may be involved in the pathogenesis of Parkinson's disease (PD). We investigated the association of Rep1 microsatellite and RsaI T-to-C substitution in the alpha-synuclein promoter region with the risk of PD by a case-control study. The RsaI C/C genotype and C allele were found less frequently in PD patients than in controls. A reduced risk of the Rep1-RsaI 0-C haplotype (OR = 0.57, 95% CI = 0.36-0.90) with PD was evident. The quantitative real-time PCR study showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…In recent years, substantial evidence has confirmed that variants in the promoter of certain genes may underlie the pathogenesis of several neurological diseases, including Parkinson's disease [Wang et al, 2006], Huntington's disease [Coles et al, 1998], and AD [Fallin et al, 2001;Heijmans et al, 2002]. Very recent studies provide strong evidence that an APP promoter polymorphism, which has a higher transcriptional activity, over-expresses APP [Lv et al, 2008].…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, substantial evidence has confirmed that variants in the promoter of certain genes may underlie the pathogenesis of several neurological diseases, including Parkinson's disease [Wang et al, 2006], Huntington's disease [Coles et al, 1998], and AD [Fallin et al, 2001;Heijmans et al, 2002]. Very recent studies provide strong evidence that an APP promoter polymorphism, which has a higher transcriptional activity, over-expresses APP [Lv et al, 2008].…”
Section: Discussionmentioning
confidence: 97%
“…Families with mutated α-syn exhibit autosomal dominant PD (Athanassiadou et al, 1999;Kruger et al, 1998;Polymeropoulos et al, 1997;Zarranz et al, 2004), and gene multiplication leading to increased wildtype α-syn levels also causes disease (Singleton et al, 2003). Certain α-syn promoter polymorphisms are PD risk factors, suggesting that even modest increases in expression can predispose to disease (Farrer et al, 2001;Kruger et al, 1999;Pals et al, 2004;Tan et al, 2000;Wang et al, 2006). In patients without genetic mutations, α-syn is found in Lewy bodies and degenerating neurites (Irizarry et al, 1998;Spillantini et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that the À110 A/C may be a functional polymorphism in the 5 0 promoter region of HSP70-1 and may affect the susceptibility to PD [Wu et al, 2004], that RsaI T-to-C substitution may have a functional relevance to the susceptibility of PD [Wang et al, 2006] and that tumor necrosis factor-a promoter polymorphism, À1031 CC, is associated with the risk of PD . Given that multi-factors involving both genetics and environment are implicated in the pathogenesis of PD, in the present study, we examined the impact of BDNF and NR4A2 genetic variations on the susceptibility to Taiwanese PD.…”
Section: Discussionmentioning
confidence: 99%
“…A portion of the subjects had been enrolled in three previously reported studies [Wu et al, 2004Wang et al, 2006]. All patients exhibited at least two of the four cardinal signs of PD: resting tremor, cogwheel rigidity, bradykinesia, and postural reflex impairment; all were diagnosed with probable idiopathic PD according to the published criteria [Gelb et al, 1999].…”
Section: Subjectsmentioning
confidence: 99%